2016
DOI: 10.1089/ham.2015.0098
|View full text |Cite
|
Sign up to set email alerts
|

High Altitude and Acute Mountain Sickness and Changes in Circulating Endothelin-1, Interleukin-6, and Interleukin-17a

Abstract: HA leads to endothelial activation and an inflammatory response. The rise in ET-1 and IL-6 is heavily influenced by the degree of exercise and hypoxia. ET-1 is an independent predictor of both AMS and its severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 36 publications
2
45
0
Order By: Relevance
“…In the current study, the additional protein provided to the HP group was almost completely oxidized (0.95 6 0.32 g protein/kg/d more than in the SP group), precluding a sustained anabolic response to protein-containing meals and negating the FFM-sparing effects of the HP diet. The increase in whole-body PS at acute HA compared to SL is consistent with other studies showing increased PS in response to acute stress (17,42,43), which may be related to increased synthesis of acute phase proteins at HA (44). The observed suppression of both PS and PB at chronic HA is consistent with that in previous reports of whole-body protein kinetics during prolonged ED at SL (41,45,46), which indicates that protein and energy sparing are adaptive responses to sustained negative energy balance.…”
Section: Discussionsupporting
confidence: 91%
“…In the current study, the additional protein provided to the HP group was almost completely oxidized (0.95 6 0.32 g protein/kg/d more than in the SP group), precluding a sustained anabolic response to protein-containing meals and negating the FFM-sparing effects of the HP diet. The increase in whole-body PS at acute HA compared to SL is consistent with other studies showing increased PS in response to acute stress (17,42,43), which may be related to increased synthesis of acute phase proteins at HA (44). The observed suppression of both PS and PB at chronic HA is consistent with that in previous reports of whole-body protein kinetics during prolonged ED at SL (41,45,46), which indicates that protein and energy sparing are adaptive responses to sustained negative energy balance.…”
Section: Discussionsupporting
confidence: 91%
“…It has been demonstrated in previous studies that inflammatory response is associated with AMS (30, 31). In this study, we have illustrated the questions using a system-level methodology and demonstrated that genes associated with immune and inflammatory response, including chemokine and their receptors, CD and HLA molecules, and inflammatory cytokines were disturbed in AMS individuals by high-altitude exposure acutely.…”
Section: Discussionmentioning
confidence: 80%
“…In 48 trekkers studied over a 6-week ascent up to 5129 m, IL-6 and IL-17a levels were found to be significantly higher at high altitude than at sea level, and exercise led to a further significant increase in IL-6 but not IL-17 levels [50]. While IL-6 seems to be critically involved in hypoxia-induced adaptive changes in muscle metabolism [51] it remains to be established whether these responses have also a defined role in the pathogenesis of sarcopenia.…”
Section: Discussionmentioning
confidence: 89%